2021
DOI: 10.1002/adma.202008634
|View full text |Cite
|
Sign up to set email alerts
|

Large Fermi‐Energy Shift and Suppression of Trivial Surface States in NbP Weyl Semimetal Thin Films

Abstract: properties of their electronic structure to observe unique physical phenomena, such as the chiral [15][16][17] and axial-gravitational anomaly, [18] the circular photogalvanic effect, [19][20] chiral sound waves, [21][22] the surface-state enhanced Edelstein effect [23] or the recently proposed chiral Hall-effect. [24] The observation of most of these effects depends on whether the topological electronic states of the WSMs can be readily accessed. In this regard, the ability to suppress non-topological (trivia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The periodicity of the contour matches the one expected for the (110) surface termination, in agreement with previous studies [13,24,26,42]. Our data cannot resolve the presence of surface states and Fermi arcs predicted by theory [13], whose signal could be enhanced or suppressed by proper surface preparation, as similarly reported in other Weyl semimetals [43,44]. Heat-treating (TaSe 4 ) 2 I has already proved to be a viable tool to modify the band structure by partial loss of the iodine atoms at the surface [42].…”
Section: Resultssupporting
confidence: 90%
“…The periodicity of the contour matches the one expected for the (110) surface termination, in agreement with previous studies [13,24,26,42]. Our data cannot resolve the presence of surface states and Fermi arcs predicted by theory [13], whose signal could be enhanced or suppressed by proper surface preparation, as similarly reported in other Weyl semimetals [43,44]. Heat-treating (TaSe 4 ) 2 I has already proved to be a viable tool to modify the band structure by partial loss of the iodine atoms at the surface [42].…”
Section: Resultssupporting
confidence: 90%
“…A fitting of the nonzero tensor elements are shown by solid lines in Figure 2c,d, giving a good agreement with the experimental data (more details can be found in the Supporting Information). As it was recently shown that the surface states in identically fabricated NbP thin films are almost exclusively topological, due to a suppression of the trivial surfaces’ states via atomic engineering, [ 30 ] we attribute the high observed efficiency to the topological surface states of NbP, in particular as they were shown the generate extremely high signal in other topological materials. [ 42 ] Figure 2e shows the relative THG efficiency over the excitation wavelength range from 1400–1950 nm with a clear peak ≈1800 nm.…”
Section: Resultsmentioning
confidence: 78%
“…NbP (001) thin films were grown by molecular‐beam epitaxy along the [100]‐direction of atomically flat MgO substrates. [ 30 ] To compensate for the MgO–NbP lattice mismatch, a Nb seed layer is grown with an in‐plane rotation of 45° to the MgO substrate and phosphorized prior to the epitaxial growth of NbP (001). The layer growth is monitored in situ via reflection high‐energy electron diffraction (RHEED) at all stages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a) the observed open arc-like contours evolve from the Fermi-arcs and have thus topological character. The fact that only these topological surface states are observed in our films merits further investigation and will be discussed elsewhere [45]. The Fermi-level shift (ΔE) of the epitaxial films is further visualized in the second derivative plot of the AA' (panel (ii) in Figure 5c), considering the extrapolation to the band crossing point and the comparison to the shape of the bulk crystal dispersion data (inset of Figure 5c (ii)), taken from Ref.…”
Section: Resultsmentioning
confidence: 96%